Effect of Leadership Styles, Social Capital, and Social Entrepreneurship on Organizational Effectiveness of Social Welfare Organization in Malaysia: Data Screening and Preliminary Analysis - Chun Won, Ng; Yen Wan, Chong; Sharif, Mohmad Yazam (International Review of Management and Marketing, 2017)
The purpose of this paper is to discuss the process of screening, editing and preparation of initial data before any further multivariate analysis of the study concerning effect of leadership styles, social capital and social entrepreneurship on organizational effectiveness of social welfare organization in Malaysia. It is vital to conduct data screening to identify any potential violation of the basic assumptions related to the application of multivariate techniques. Moreover, initial data examination enables the researcher to gain a deeper understanding of the data collected. For this research, simple random sampling will be adopted as the sampling technique to draw conclusion about the entire population. Samples of 159 were selected from the total population of 271 welfare organization in Malaysia. Data screening and preliminary analysis were conducted to meet the assumptions of multivariate analysis. Thus, the study carried out non-response bias test, missing data detection and treatment, multivariate outliers detection and treatment, normality assessment, linearity assessment, common method variance assessment, multicollinearity assessment, homoscedasticity assessment and descriptive analysis. All the assessment was conducted using IBM SPSS statistical software version 21.0 (SPSS). In brief, the data found to fulfil the requirements for further multivariate analysis. Keywords: Organizational Effectiveness, Social Welfare Organization, Data Screening, Preliminary Analysis JEL Classifications: D23, L2